1987
DOI: 10.1029/tc006i003p00215
|View full text |Cite
|
Sign up to set email alerts
|

Overthrust emplacement of New Caledonia Ophiolite: Geophysical evidence

Abstract: Geophysical studies support inferences from outcrop geology that during the Late Eocene an ophiolite sheet exposed on New Caledonia was thrust southward over a rock complex consisting of sedimentary, volcanic, and metamorphic rocks that range in age from Pre‐Permian to Eocene. The outcropping ultramafic complex consists of a layered sequence, approximately 3000 m thick, including harzburgite, dunite, wehrlite, serpentinite, and gabbro. The absence of pillow basalts and sheeted dikes on land suggests that durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 28 publications
1
77
0
Order By: Relevance
“…Kroenke (1984) and Bitoun and Recy (1982) suggested that the South Loyalty Basin formed in the Eocene. In contrast, Dubois et al (1973) and Collot et al (1987) argued that the South Loyalty Basin formed as a marginal basin prior to 80 Ma above an east-dipping subduction zone, with a trench west of New Caledonia, implying subduction of oceanic crust of the New Caledonia Basin. New seismic interpretations of South Loyalty Basin sediment fill from the southern part of the basin away from the zone of Eocene emplacement of the New Caledonia ophiolite suggest that the South Loyalty Basin formed by extension and later ocean crust accretion around 120 Ma in the Early Cretaceous (Auzende et al 2000), perhaps contemporaneous with the opening of the New Caledonia Basin.…”
Section: Geophysical Recordmentioning
confidence: 97%
See 3 more Smart Citations
“…Kroenke (1984) and Bitoun and Recy (1982) suggested that the South Loyalty Basin formed in the Eocene. In contrast, Dubois et al (1973) and Collot et al (1987) argued that the South Loyalty Basin formed as a marginal basin prior to 80 Ma above an east-dipping subduction zone, with a trench west of New Caledonia, implying subduction of oceanic crust of the New Caledonia Basin. New seismic interpretations of South Loyalty Basin sediment fill from the southern part of the basin away from the zone of Eocene emplacement of the New Caledonia ophiolite suggest that the South Loyalty Basin formed by extension and later ocean crust accretion around 120 Ma in the Early Cretaceous (Auzende et al 2000), perhaps contemporaneous with the opening of the New Caledonia Basin.…”
Section: Geophysical Recordmentioning
confidence: 97%
“…Collot et al (1987) have invoked east-dipping subduction west of New Caledonia from 80 Ma to Early Paleocene (ca 64 Ma), although there are presently no known rocks of this age with subductionrelated signatures to support this model. Sdrolias et al (2002) also argued for a long period of east-directed subduction east of the Lord Howe Rise during the period from around 90 Ma until about 45 Ma.…”
Section: Fragmentation Of Continental Crust Over a Retreating Slab Eamentioning
confidence: 99%
See 2 more Smart Citations
“…In that sense, they provide a unique opportunity to study the physical and chemical processes that affect the upper mantle in mid oceanic and subduction environments. The Cretaceous to Eocene New Caledonia ophiolite is an extensive and very well-exposed mafic-ultramafic complex ( [Avias, 1967], [Collot et al, 1987] and [Prinzhofer, 1981]) that is still partially connected to the modern oceanic floor of the South Loyalty Basin to the east of the island (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%